Pengaruh Tepung Cangkang Kerang Hijau dan Pupuk KNO3 Terhadap Pertumbuhan dan Hasil Kedelai Edamame pada Tanah Gambut - Amanda, Tasya; Listiawati, Agustina; Zulfita, Dwi (Fakultas Pertanian Universitas Tanjungpura, 2025)
The Impact of Green Mussel Shell Powder and KNO3 Fertilizer On the Growth and Yield of Edamame Soybean In Peat Soil. In Indonesia, edamame soybeans are a healthy and nutritious food choice, utilized as a new business opportunity in the soy-based food and beverage industry. Peat soil, as a planting medium, faces low pH levels, limiting nutrient availability. Green mussel shell flour can serve as an alternative material to neutralize soil acidity in peat soil because it contains calcium carbonate, which neutralizes peat soil acidity. This study aims to determine the best interaction dose of green mussel shell flour and KNO₃ fertilizer on the growth and yield of edamame plants in peat soil. The research was conducted in Southeast Pontianak District, Pontianak City, West Kalimantan. This research took place from August 2024 to November 2024. The design used in this study was a Factorial Completely Randomized Design (RAL) consisting of 2 treatments. The first factor was green mussel shell flour (K), consisting of 3 treatment levels: 0.84 tons/ha, 1.64 tons/ha, and 2.44 tons/ha, while the second factor was KNO₃ fertilizer (P), consisting of 3 treatment levels: 300 kg/ha, 450 kg/ha, and 600 kg/ha. Each treatment was repeated 3 times. The variables observed in this study included: plant height, root volume, plant dry weight, number of productive branches, number of pods per plant, pod weight per plant, number of empty pods per plant, and number of filled pods per plant. The results showed an interaction between the application of green mussel shell flour and KNO₃ fertilizer on the root volume and dry weight of edamame soybeans in peat soil. The application of green mussel shell flour at a dose of 0.84 tons/ha and KNO₃ fertilizer at a dose of 300 kg/ha, as well as the application of green mussel shell flour at a dose of 2.44 tons/ha and KNO₃ fertilizer at a dose of 300 kg/ha, showed an efficient dose on root volume, which was 21.33 cm3, and plant dry weight, which was 26.71 g/plant.adalah Rancangan Acak Lengkap Fakrorial (RAL) yang terdiri dari 2 perlakuan. Faktor pertama yaitu tepung cangkang kerang hijau (K) yang terdiri dari 3 taraf perlakuan yaitu 0,84 ton/ha, 1,64 ton/ha, dan 2,44 ton/ha, sedangkan faktor kedua yaitu pupuk KNOâ‚ƒ (P) yang terdiri dari 3 taraf perlakuan yaitu 300 kg/ha, 450 kg/ha, dan 600 kg/ha. Masing masing perlakuan diulang sebanyak 3 kali dengan setiap ulangan terdiri dari 4 tanaman sample, sehinga jumlah tanaman seluruhnya adalah 108 tanaman. Variable yang diamati dalam penelitian ini meliputi: tinggi tanaman, volume akar, berat kering tanaman, jumlah cabang produktif, jumlah polong pertanaman, berat polong pertanaman, jumlah polong hampa pertanamna, dan jumlah polong isi pertanaman. Hasil penelitian menujukan bahwa Terjadi interaksi antar pemberian tepung cangkang kerang hijau dan pupuk KNO3 terhadap volume akar dan berat kering tanaman kedelai edamame pada tanah gambut. Pemberian tepung cangkang kerang hijau dengan dosis 0,84 ton/ha dan pupuk KNO3 dengan dosis 300 kg/ha serta pemberian tepung cangkang kerang hijau dengan dosis 2,44 ton/ha dan pupuk KNO3 dengan dosis 300 kg/ha menunjukkan dosis efisien terhadap terhadap volume akar yaitu 21,33 cm3 dan berat kering tanaman yaitu 26,71 g/tanaman.